Morphology, fractal dimension, size and nanostructure of exhaust particles from a spark-ignition direct-injection engine operating at different air–fuel ratios. (1st December 2016) - Wu, Zhaoyang; Song, Chonglin; Lv, Gang; Pan, Suozhu; Li, Hao
Highlights: Physicochemical characteristics of SIDI particles were studied at different AFRs. Fractal dimensions decreased with increases in the AFR after an initial increase. The largest average primary particle diameter was obtained at an AFR of 14.7. The nanostructures of SIDI soot particles were affected by the AFR. The soot particles at AFR = 14.7 exhibited the lowest sp 2 /sp 3 hybridization ratio. Abstract: This work studied the physicochemical characteristics of exhaust particles from a 1.48 L SIDI engine operating at different air–fuel ratios (AFRs). The morphology, fractal dimension, size and nanostructure were characterized using high-resolution transmission electron microscopy (HRTEM) in conjunction with electron energy-loss spectroscopy. The results indicate that SIDI aggregate particles produced at varying AFRs exhibit different morphologies. TEM images show that the aggregates obtained at an AFR of 14.7 are more compactly clustered than those generated under fuel-rich and fuel-lean conditions. The fractal dimension of SIDI aggregates at an AFR of 14.7 is found to be 2.21, a value that is larger than those from other AFRs. The primary particle sizes are distributed over a wide range of 5–55 nm at all AFRs, although the largest average primary particle diameter is found at an AFR of 14.7. Similar to diesel soot particles, SIDI soot particles also show characteristic shell-core and turbostratic structures at the nanoscale level. At an AFR of 14.7, the soot particles have a relatively short fringe length, a small fringe separation distance and high fringe tortuosity. As the AFR is increased, the sp 2 /sp 3 hybridization ratios first gradually decrease and then increase, with a minimum value of 0.156 at AFR = 14.7. SIDI soot particles are likely more reactive than diesel soot particles because they possess the relatively short fringe length, large separation distance and high tortuosity.